Implementation of The State Border Area Development Policy In Aruk Sambas District West Kalimantan Province - Siddiq, Bakri; Hamdi, Muchlis; Budi Santoso, Eko; Puspita E, Diah (Ridwan Institute, 2024)
The phenomenon that becomes the object of research is the implementation of the state border area development policy in Aruk, Sambas Regency, West Kalimantan Province. This research aims to analyze the implementation of the state border area development policy in Aruk, Sambas Regency, West Kalimantan Province and formulate a state border area development model in Aruk, Sambas Regency, West Kalimantan Province. The research method used a descriptive qualitative approach. The determination of research informants was carried out through the snowball technique. The results showed that the management of strategic issues in the state border area until now lacks the active role of Ministries/ Institutions and Local Governments. The implementation of development by K/L is still concerned with sectoral ego, this can be evidenced by the large disparity between the Implementation of the BWN-KP Management Master Plan 2020-2024 with programs/activities and budgets of Ministries/Institutions that have been committed to the implementation of development in state border areas in priority location sub-districts, PKSN, PLBN and PPK. Referring to the above, the activities of the Aruk PLBN Border Area Development of Sambas Regency are still categorized as not optimal. Supporting and inhibiting factors for the development of the Aruk PLBN area include the Aruk PLBN Management Resource Factor, the Human Resources Competency Factor, the Information and Technology Support Factor and the Aruk PLBN Management Positive Attitude Factor. Meanwhile, the inhibiting factors of development at PLBN Aruk Sambas Regency include Communication Factors, Infrastructure Factors and Bureaucratic Factors. The development model of border area development of PLBN Aruk Sambas Regency is the institutional development of the Border Management Agency consisting of institutional authority, institutional structure, institutional personnel, and institutional administrative resource management